Analisis Kualitas Sistem Drainase terhadap Bencana Banjir di Distrik Abepura Kota Jayapura: Studi Kasus : Kelurahan Way Mhorock, Distrik Abepura - Muhammad Ilham; Monita Y. Beatrick; Irja T. Simbiak (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Flood disaster is the most frequent disaster in Indonesia. Based on BNPB records throughout 2021, flood disasters have occurred 1,279 times. Poor drainage system can be one of the factors causing flood disasters. Way Mhorock Village, Abepura District is one of the areas that has poor drainage network quality. This is because Way Mhorock Village is one of the centers of community activities, so it has the potential to cause flooding. This study examines the quality of the drainage system against disasters in Abepura District by focusing on Way Mhorock Village. The research methods used to achieve the objectives in this research are qualitative methods, spatial analysis, and analytical hierarchy process. Qualitative descriptive analysis method to assist and describe the actual drainage problems in the field in the form of pictures. Spatial analysis method using GPS by recording problematic drainage points then processed using ArcGIS software. Analytical Hierarchy Process method by capture the perspective of stakeholders from the agency to determine the assessment of the quality level of the drainage system that has the potential to cause flooding in Way Mhorock Village. The results showed that there are 4 problems that affect the quality of drainage in Way Mhorock Village, namely drainage sedimentation, land use change, drainage cross section, and the volume of waste found at 33 points in Way Mhorock Village. Based on the results of the analytical hierarchy process using an expert choice application, drainage sedimentation is the most influential criterion on improving drainage quality with alternative handling provided in the form of law enforcement policies against environmental violations by the community.